An empirical examination of family-managed firms and non-family-managed firms: evidence from Malaysia - Mustapha, Mazlina; Imam Muslim, Zurimah (Universiti Putra Malaysia Press, 2013)
The purpose of this study is to explore the firm characteristics of family-managed firms in Malaysian public-listed firms. Selected firms were matched for size and industry before comparisons were made between the family-managed firms and non-family-managed firms. The data were collected using secondary sources. Various firm characteristics were investigated. The findings indicate that firms managed by families have a significantly larger board size, higher number of non-independent directors and executive directors and their directors have significantly longer experience working in the firm. However, the results suggest that the directors of these family-managed firms significantly lack professional qualification and tend to have fewer meetings compared to those directors in non-family-managed firms. The findings also indicate that the compensations paid to the executive directors of family-managed firms are significantly higher than those paid to executive directors of non-family managed firms. The results also suggest that these firms have not utilised their assets efficiently to generate sales compared to their non-family-business counterparts.